2005
DOI: 10.1007/s00442-005-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Females make tough neighbors: sex-specific competitive effects in seedlings of a dioecious grass

Abstract: If males and females of a species differ in their effect on intraspecific competition then this can have significant ecological and evolutionary consequences because it can lead to size and mortality disparities between the sexes, and thus cause biased population sex ratios. If the degree of sexual dimorphism of competitive effect varies across environments then this variation can generate sex ratio variation within and between populations. In a California population of Distichlis spicata, a dioecious grass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 33 publications
4
53
0
Order By: Relevance
“…Additionally, variation in edge pore density in males was signiWcantly associated with several variables in the path diagram, indicating an importance of edge pore density to male responses. The pattern of males being in more stressful patches relative to females is consistent with patterns found in seed plants (Freeman et al 1976;Bierzychudek and Eckhart 1988;Dawson and Ehleringer 1993;Dawson and Geber 1999;Eppley 2001Eppley , 2006Dudley and Galen 2007), in the moss genera Splachnum (Cameron and Wyatt 1990), but inconsistent with the moss S. caninervis, where males and females co-occur in the shade but males are absent in open, high-light sites (Stark et al 2005a). However, males of S. caninervis were recently found to regenerate better than females after heat stress (Stark et al 2008).…”
Section: Relationship Of Sex-speciwc Traits Responses To Environmentasupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, variation in edge pore density in males was signiWcantly associated with several variables in the path diagram, indicating an importance of edge pore density to male responses. The pattern of males being in more stressful patches relative to females is consistent with patterns found in seed plants (Freeman et al 1976;Bierzychudek and Eckhart 1988;Dawson and Ehleringer 1993;Dawson and Geber 1999;Eppley 2001Eppley , 2006Dudley and Galen 2007), in the moss genera Splachnum (Cameron and Wyatt 1990), but inconsistent with the moss S. caninervis, where males and females co-occur in the shade but males are absent in open, high-light sites (Stark et al 2005a). However, males of S. caninervis were recently found to regenerate better than females after heat stress (Stark et al 2008).…”
Section: Relationship Of Sex-speciwc Traits Responses To Environmentasupporting
confidence: 76%
“…The underlying mechanisms to account for sex-speciWc demographies are thought to result from the diVering male vs. female sexual reproductive functions and the tradeoVs associated with these functions and other life history traits Obeso 2002;Case and Ashman 2005). Nevertheless, few studies have linked SSS to variation in sex-speciWc ability to occupy diVerent ranges of the gradients [but see Eppley (2006) for an example of sex-speciWc competitive ability that varies with habitat]. Here, we test for sex-speciWc physiological and related morphological responses that are linked to observed patterns of SSS in a dioecious bryophyte, Marchantia inXexa.…”
Section: Introductionmentioning
confidence: 99%
“…plastic alteration of sex expression in relation to its environment) (Cox 1981;Bierzychudek & Eckhart 1988;Eppley, Stanton & Grosberg 1998). Spatial segregation of the sexes can also be the result of interactions with other species such as competition for limited resources (Freeman, Klikoff & Harper 1976;Cox 1981;Eppley 2006;Mercer & Eppley 2010). Inter and intrasexual competition has been proposed as one of the probable mechanisms behind local spatial segregation of the sexes (Bertiller, Sain & Carrera 2002b;Eppley 2006;Mercer & Eppley 2010).…”
mentioning
confidence: 99%
“…Spatial segregation of the sexes can also be the result of interactions with other species such as competition for limited resources (Freeman, Klikoff & Harper 1976;Cox 1981;Eppley 2006;Mercer & Eppley 2010). Inter and intrasexual competition has been proposed as one of the probable mechanisms behind local spatial segregation of the sexes (Bertiller, Sain & Carrera 2002b;Eppley 2006;Mercer & Eppley 2010). Nevertheless, there has been a conspicuous lack of investigation into sex-related effects on the competitive interaction with other plant species (S anchez-Vilas, Turner & Pannell 2010).…”
mentioning
confidence: 99%
“…Results obtained by Marciniuk et al (2010) demonstrated that female individuals of Aruncus sylvestris had markedly higher habitat requirements compared with the males. Eppley (2006) revealed that in Distichlis spicata a variation in the sex ratio could be caused by the differences in competitive abilities at the seedling stage, with female seedlings exhibiting a stronger environment dependent competitive ability than male seedlings. It was suggested that sex-specific competitive differences could have a greater impact on seedlings, and research was needed to explain if such competitive interactions occured at the vulnerable seedling stage.…”
Section: Discussionmentioning
confidence: 99%